Book reviews - Trautner-Kromann, Hanne; Wagner, Thorsten; Hagensen, Lars; Rian, Dagfinn; Røllum-Larsen, Claus (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
The Oxford handbook of Jewish studies (Edited by Martin Goodman. Associated editors Jeremy Cohen & David Sorkin, 2002) is reviewed by Hanne Trautner-Kromann.Juden, Bürger, Deutsche. Zur Geschichte von Vielfalt und Differenz 1800–1933 (eds. Andreas Gotzmann, Rainer Liedtke, Till van Rahden, 2001) is reviewed by Thorsten Wagner.Frie jøder? Forholdet mellem kristne og jøder i Danmark fra Frihedsbrevet 1814 til Grundloven 1849. Kirkehistoriske studier, III. række nr. 10 (Martin Schwarz Lausten, 2005) is reviewed by Lars Hagensen.Jødene fra Trondheim (Jon Reitan, 2005) is reviewed by Dagfinn Rian.A fusion of traditions. Liturgical music in the Copenhagen synagogue. University of Southern Denmark Studies in History and Social Sciences vol. 310 (Jane Mink Rossen & Uri Sharvit, 2006) is reviewed by Claus Røllum-Larsen.